Study of the High Resolution Spectrum of the S18O16O Molecule in the Hot 2ν2 + ν3 - ν2 Band; Russian Physics Journal; Vol. 61, iss. 1 - Zyatkova (Ziatkova) A. G. Anastasiya Georgievna (2018, 2018)
Title screen